Autoimmunity and autoinflammation — the key to understanding the pathogenesis of osteoarthritis and developing new ways for its prevention and therapy - I. V. Sarvilina; A. M. Lila; L. I. Alekseeva; O. A. Gromova; E. A. Taskina (Современная ревматология)
The review considers the full spectrum of currently known autoantigens in osteoarthritis (OA) and discusses their role in the development and/or persistence of synovitis and the initiation of subsequent destruction of articular cartilage with the development of an autoimmune response and auto-inflammation. Of great interest are methods of drug prevention of OA considering autoimmunity responses and associated auto-inflammation, including the use of pharmaconutraceuticals.Preclinical and clinical studies of the safety and efficacy of pharmaconutraceuticals containing native type II collagen are presented. A clear relationship between the composition/chemical structure of the collagen components and its mechanism of action and efficacy is discussed. Taking into account the autoimmune pathogenesis of OA, new combined pharmaconutraceuticals aimed at reducing the manifestations of autoinflammation (chondroitin sulfate, glucosamine sulfate) are developed. They have an optimal ratio of active ingredients with a sufficient level of evidence, which allows enhancing their beneficial pharmacological effects.